Synthesis of polydisulphide via iodine oxidation for self-healing applications - Thuy Thu Truong; Le-Thu T. Nguyen (Vietnam Journal of Science, Technology and Engineering, 2025)
Self-healing materials with scratch-healing capabilities have garnered significant attention in recent years. Among the various reversible bonds investigated as healing mechanisms in polymer materials, dynamic disulphide chemistry has been particularly appealing. This study reports the synthesis of a polydisulphide as a healing segment, incorporating reversible disulphide bonds for self-healing applications. The polydisulphide was synthesised through the oxidation of a telechelic mercaptan compound, employing iodine as the oxidising agent. The resulting polydisulphide was characterised by proton nuclear magnetic resonance (1H NMR) and Fourier transform infrared spectroscopy (FT- IR). It was then crosslinked with telechelically acrylate end-capped polycaprolactone and a tetrathiol crosslinker via the thiol-acrylate Michael addition reaction, forming a self-mendable network. The network was further characterised using FT-IR, differential scanning calorimetry, optical microscopy, and tensile testing. Optical microscopy confirmed the network’s scratch-healing ability, while tensile testing demonstrated a strength recovery of 62% after scratching and subsequent healing at 100oC for 24 hours.